Economic implications of localization strategies for cerebrospinal fluid rhinorrhea. Issue 3 (12th December 2019) - Pool, Christopher D.; Patel, Vijay A.; Schilling, Amber; Hollenbeak, Christopher; Goyal, Neerav
Abstract : Background: The direct costs associated with different diagnostic algorithms to localize cerebrospinal fluid (CSF) rhinorrhea have not been described. Methods: A decision‐tree analysis of imaging modalities used to localize CSF rhinorrhea was performed to compare associated direct costs. The primary outcome was cost, which was determined based on reimbursement data published by the Centers for Medicare and Medicaid Services in 2018. The model was parameterized after a literature review of published studies was performed from 1990 to 2018 to estimate the sensitivity CSF rhinorrhea localization of the following radiographic modalities: high‐resolution computed tomography (HRCT), magnetic resonance cisternography (MRC), and CT cisternography (CTC). In addition to base case analysis, 1‐way sensitivity analyses were also performed to evaluate the robustness of results to changes in model parameters. Results: Among patients with a high suspicion for CSF rhinorrhea, use of HRCT followed by exploration in the operating room if preliminary HRCT was negative was found to be the optimal localization modality from a cost perspective ($172.25). The next least costly algorithm was HRCT followed by MRC ($294.10). Imaging algorithms beginning with CTC were the next least costly modality ($727.37). Sensitivity analyses generally supported HRCT to be the optimal initial radiographic strategy over a wide range of parameter values. Conclusion: This work advocates HRCT as first‐line modality to localize CSF rhinorrhea from a cost perspective. Although algorithms beginning with MRC were on average $35 more expensive than those starting with CTC, associated risks of CTC were not modeled and may play a role in decision making.